Amir Apple Variety - Kadyrova Mamlakat Muminovna (Zien Journals, 2022)
Amir alimkhon and mangit khukumdori are mentioned in this article. Said Mir Muhammad Alimkhon is the last Uzbek ruler who ruled the emirate of Bukhara in 1919920. He was born on January 3, 1880 in Bukhara.
Keywords: Amir Alimkhan; The Turks; Said Muhammad